2021
DOI: 10.3390/cryst11111354
|View full text |Cite
|
Sign up to set email alerts
|

Selenium/Chitosan-Folic Acid Metal Complex Ameliorates Hepatic Damage and Oxidative Injury in Male Rats Exposed to Sodium Fluoride

Abstract: Continuous exposure to sodium fluoride (NaF) imbalances the oxidative status in the body. The current study investigated the effect of the selenium/chitosan-folic (Se/chitosan-folic acid) novel metal complex on oxidative injury and tissue damage in the hepatic tissues of male rats exposed to (NaF). Male rats received NaF (10.3 mg/kg) and Se/chitosan-folic acid (0.5 mg/Kg) orally for successive 30 days. Male rats exposed to NaF showed multi-histopathological alterations in the hepatic tissues including degenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Oxidative stress is related to the decline in insulin secretion, and pancreatic tissues are more susceptible to oxidative stress because of their low antioxidant enzyme levels [33]. The treatment applied in our study elevated the antioxidant enzyme levels significantly when compared with those in STZ-treated groups, indicating that the current results support the previously obtained results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Oxidative stress is related to the decline in insulin secretion, and pancreatic tissues are more susceptible to oxidative stress because of their low antioxidant enzyme levels [33]. The treatment applied in our study elevated the antioxidant enzyme levels significantly when compared with those in STZ-treated groups, indicating that the current results support the previously obtained results.…”
Section: Discussionsupporting
confidence: 90%
“…I observed that increased lipid peroxidation in the STZ (untreated diabetic) group could include oxidative stress [33]. It was found that VOSO 4 combined with selenium tetrachloride protects pancreatic tissues from lipid peroxidation generation and from any changes in CAT, SOD, and MDA (a marker of peroxidation) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium (Se) is shown to be reduced in patients with chronic liver diseases [11]. Se is an essential trace element for humans [12]; it is essential for the antioxidant defense system [13].…”
Section: Introductionmentioning
confidence: 99%
“…The NLRP3 pathway contains three proteins and they do not cause inflammation when these three proteins are dissociated in cells [47]. Only when sensing pathogen-associated molecules or danger-associated molecules, the three proteins will gather together to assemble NLRP3 inflammatory bodies and induce inflammation, the ASC (apoptosisassociated speck-like protein containing a CARD) in the nucleus will be released into the cytoplasm as a protein bridge recognition adapter, and its N-terminal PYD will bind to the NLRP3 through oligomerization [48].…”
Section: Nlrp3 Inflammatory Pathwaymentioning
confidence: 99%